How Large Is the Gender Dividend? Measuring Selected Impacts and Costs of Gender Inequality - Wodon, Quentin; Onagoruwa, Adenike; Malé, Chata; Montenegro, Claudio; Nguyen, Hoa; de la Brière, Bénédicte (World Bank, Washington, DC, 2020)
Reducing gender inequality makes economic sense apart from being the right thing to do. Achieving gender equality and empowering all women and girls is the fifth sustainable development goal and is a top priority for governments. Countries can achieve this goal if they take appropriate steps. This note is part of a series that aims to measure the economic cost of gender inequality globally and regionally by examining the impacts of gender inequality in a wide range of areas and the costs associated with those impacts. Given that gender inequality affects individuals throughout their life, economic costs are measured in terms of losses in human capital wealth, as opposed to annual losses in Gross Domestic Product (GDP) or GDP growth. The notes also aim to provide a synthesis of the available evidence on successful programs and policies that contribute to gender equality in multiple areas and achieve the Sustainable Development Goals (SDGs).